Data analysis of 287 patients present with erythema nodosum: A closer look at associations - Oktem Ayse; Incel Uysal Pinar; Sahin Buket; Yalcin Basak (Our Dermatology Online, 2018)
Background: Erythema nodosum (EN) is the most common clinical variant of panniculitis. It may occur in association with a wide variety of causative stimuli. The aim of our study is to describe the possible etiologic factors associated with EN and compare them with the series previously reported in the literature. Materials and Method: This is a retrospective chart review of 287 patients who have presented to our clinic with tender erythematous nodular lesions and finally diagnosed as eythema nodosum between January 2010 and December 2015. Results: Our retrospective study included 239 females and 48 males (sex ratio, 5:1). Of the 287 EN patients, etiologic factor has been determined in 123 (42.85%) of the participants and this group was categorized as secondary EN. In secondary EN group the leading etiologic factor was infections (n=68, 23.69%). Other etiologic factors were Behcet's Disease (n=18, 6.27%), connective tissue disease (n=8, 2.78%), tuberculosis (n=6, 2.09%) sarcoidosis (n= 5, %1.74), drugs (n=6, 2.09%), granulomatous mastitis (n=2, 0.69%), IBD (n=2,0.69%), malignancy (n=1, 0.34%) and food supplement (n=1, 0.34%). Conclusion: Our data confirm that viral and bacterial infections are the leading causative factors of EN, followed by Behcet's Disease, pregnancy and connective tissue disease (CTD). These conditions should be investigated as part of systemic search.